2006
DOI: 10.1007/s00253-005-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric dimethyl sulfide sensor using Rhodovulum sulfidophilum cells based on intrinsic pigment conversion by CrtA

Abstract: A colorimetric whole-cell sensor for dimethyl sulfide (DMS) was constructed based on the in vivo conversion of intrinsic pigments in response to the analyte. In a marine bacterium, Rhodovulum sulfidophilum, carotenoids are synthesized via the spheroidene pathway. In this pathway, demethylspheroidene, a yellow carotenoid, is converted to spheroidene under catalysis of O-methyltransferase. Spheroidene monooxygenase (CrtA) catalyzes the terminal step of the pathway and converts spheroidene to spheroidenone, a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…To overcome these drawbacks, bacterial whole-cell biosensors using natural pigment as the biosensor output have been reported. A red pigment biosynthetic gene (crtA) of Rhodovulum sulfidophilum was used for arsenite and dimethyl sulfide detection [23,24]. A bluegreen pigment synthesis of Pseudomonas aeruginosa was used for N-butyryl homoserine lactone detection [22].…”
Section: Detection Of CD By Red Color Developmentmentioning
confidence: 99%
“…To overcome these drawbacks, bacterial whole-cell biosensors using natural pigment as the biosensor output have been reported. A red pigment biosynthetic gene (crtA) of Rhodovulum sulfidophilum was used for arsenite and dimethyl sulfide detection [23,24]. A bluegreen pigment synthesis of Pseudomonas aeruginosa was used for N-butyryl homoserine lactone detection [22].…”
Section: Detection Of CD By Red Color Developmentmentioning
confidence: 99%
“…The bacterial color change in crtIBS was stable under both anaerobic and aerobic preculture conditions. In contrast, the bacterial color change in crtA-based biosensors is very sensitive to dissolved oxygen in the culture medium (14). Therefore, our findings demonstrate that crtIBS could be used for water samples containing various oxygen concentrations.…”
Section: Discussionmentioning
confidence: 64%
“…We recently reported that a carotenoid biosynthesis gene, crtA, can also be used as a novel reporter in whole-cell biosensors made from Rhodovulum sulfidophilum (9,14). Two crtAbased biosensors have been established by disrupting the crtA gene and reintroducing it downstream of a DNA response element.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reporter genes encoding enzymes, enzymatic complexes or fluorescent proteins have been used to construct whole-cell biosensors such as ␤ -galactosidase, the wellknown protein reporter for which numerous colorimetric substrates are available, and also the green fluorescent proteins, luciferase [Stocker et al, 2003], alkaline phosphatase [Kohler et al, 2000] or, as recently proposed, carotenoid [Maeda et al, 2006] or pyocyanin [Fletcher et al, 2007] synthesis systems. Crucial criteria for choosing or building a biosensor include sensitivity, time needed, portability, robustness and eventual reusability.…”
Section: Introductionmentioning
confidence: 99%